PELAKSANAAN PENEGAKAN HUKUM TINDAK PIDANA PEMALSUAN SERTIFIKAT TANAH DI WILAYAH HUKUM KOTA PEKANBARU - Putra, Dondy Permana; ', Firdaus; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Land certificates issued by agencies of the National Land Agency, or BPN have signs or traits that have so hard to forge its own identity in any official document issued by BPN. Confidentiality and authenticity in official documents BPN, maintained quality through special safeguards contained in the document. Can be in the form of the use of special paper, sealing tape, use of special inks, and so forth. The function of different types of safety is to prevent crimes related to forgery of documents. Thus, when there is a suspicion of allegedly false land titles, can be analyzed in a way comparable to the original document that has the security standards. But with technological advances handful of people who abuse the existing technology by making it a crime to the means. One of them is falsification of land titles.The purpose of this thesis, namely; First, to determine the role of the police as well as the relevant parties to the crime of counterfeiting law enforcement certificate of land in the resort city of Pekanbaru police law. Second, to find out why the occurrence of the crime of falsification of certificates of land in the resort city of Pekanbaru police law. Third, To know the efforts made by the police and other interested parties on the prevention of the crime of falsification of certificates of land in the resort city of Pekanbaru police law.This type of research is a juridical sociological research, because the author directly examine the problems that occur. This research was conducted in the City Police Pekanbaru, while the sample population is a whole party related to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this study with interviews, literature study and observation.From the research there are three main issues that can be inferred. First, many cases of forgery of certificates in the city this pekanbaru which has not been revealed or reported. Second, the internal and external factors that hinder enforcement of the law against the crime of counterfeiting this certificate, the lack of evidence, lack of testimony from witnesses as well as well as the lack of clarity about the status of the land. Thirdly, the intention of seeking its own advantage by falsifying land titles be causing the crime of falsification of this certificate. Suggestions writer, first, it must improve the performance of Pekanbaru City Police in dealing with the crime of forgery of certificates. Secondly, facilitates finding info on the status of land and checking the authenticity of land titles in the National Land Agency.Keywords: Law Enforcement - Crime - Fraud - Certificate